2004
DOI: 10.1111/j.1440-1746.2004.03370.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of bilirubin uridine diphosphate‐glucuronosyltransferase gene in Japanese patients with Crigler–Najjar syndrome or Gilbert's syndrome as well as in healthy Japanese subjects

Abstract: Polymorphisms in the coding region of UGT1A1 were commonly observed in Japanese patients with GS and in healthy subjects. The genetic basis of hyperbilirubinemia appears to be different between the Japanese and Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 21 publications
7
74
1
2
Order By: Relevance
“…Narter et al [1] have not looked into the influence of the TA insertion in the TATA box of the promoter region in the UGT1A1 gene on the development and severity of hyperbilirubinemia, whereas we found that the G71R mutation along with the TA insertion (either in TA6/7 or TA7/7) had a significant effect on unconjugated bilirubin levels and the severity of neonatal hyperbilirubinemia in our patients (data not shown). This finding is in agreement with those reported among the Japanese neonates [4] but discordant with the results on Gilbert's syndrome patients from the eastern part of India [5]. On the other hand, a complete absence of this mutation was observed among the neonates with or without hyperbilirubinemia from north India [6].…”
Section: To the Editorsupporting
confidence: 90%
“…Narter et al [1] have not looked into the influence of the TA insertion in the TATA box of the promoter region in the UGT1A1 gene on the development and severity of hyperbilirubinemia, whereas we found that the G71R mutation along with the TA insertion (either in TA6/7 or TA7/7) had a significant effect on unconjugated bilirubin levels and the severity of neonatal hyperbilirubinemia in our patients (data not shown). This finding is in agreement with those reported among the Japanese neonates [4] but discordant with the results on Gilbert's syndrome patients from the eastern part of India [5]. On the other hand, a complete absence of this mutation was observed among the neonates with or without hyperbilirubinemia from north India [6].…”
Section: To the Editorsupporting
confidence: 90%
“…The frequency of the UGT1A1*28 allele varies according to ethnic group. This variant is expressed less frequently in Asians (Japanese 11% and Chinese 16%) than in whites (36 -39%) and African Americans (43%) (Beutler et al, 1998;Ki et al, 2003;Takeuchi et al, 2004). Several studies have shown that the incidence of hyperbilirubinemia in patients exposed to atazanavir or indinavir varies as a function of genotype.…”
Section: Pharmacokinetics Of Udp-glucuronosyltransferase and The Riskmentioning
confidence: 99%
“…The UGT1A1*6 polymorphism, which is found in Asians (13-23%) and rarely in whites (Ͻ.1%), is associated with a 70% in vitro reduction of the rate of bilirubin conjugation and as such mimics Gilbert's syndrome (Bosma et al, 1995;Yamamoto et al, 1998;Takeuchi et al, 2004;Kaniwa et al, 2005;Urawa et al, 2006). Boyd et al (2006) reported that the risk of severe hyperbilirubinemia with indinavir was correlated with the presence of the UGT1A1*6 allele in Thai patients.…”
Section: Pharmacokinetics Of Udp-glucuronosyltransferase and The Riskmentioning
confidence: 99%
“…Arrows highlight variants previously shown to be associated with human-health phenotypes in either multiple human subject studies or in individual association studies involving more than 100 human subjects; these include the UGT1A8*2 allele, 70,71 the three non-synonymous coding SNPs in UGT1A7 (*2,*3,*10), 69,72,73,81,82 two nsSNPs in UGT1A6 (*2,*3), 67,68,70 rs887829 -the SNP revealing the strongest association with tranilast-induced hyperbilirubinemia, 28 and the UGT1A1*6 allele. 10,24,25,[50][51][52][53][54][55][56][57][83][84][85][86][87] Figure 4 Two-point LD maps for variants of UGT1A1, UGT1A6, and UGT1A9 mapped by population. The patterns of pairwise LD, summarized by |D 0 |, include 60 variants in African-Americans (left), 52 in European-Americans (center), and 49 in Asians (right).…”
Section: Prediction Of Functional Effects Of Amino-acid Replacement Vmentioning
confidence: 99%